Utilizing English Learning Videos as a Technological Innovation at Moch Sroedji University, Jember - Faridha, Noor; Nurul Afidah; Ika Purnama Sari; Hazairin Nikmatul Lukma (CV. Media Digital Publikasi Indonesia, 2024)
The purpose of this study is to address the challenges faced by English teachers in teaching English in grade XI. In addition, to improve students' motivation and academic achievement. In the context of globalization. English language skills, especially speaking skills, have become a necessity. The methods used are lectures and classroom practice. The target of this service is SMA AL-AFLAH Silo Jember which targets 30 students from grade XI. The findings indicate that video resources significantly increase students' motivation and active interaction as well as engagement and comprehension, indicating that the integration of multimedia devices can revolutionize English education. This study contributes to the pedagogical discourse by offering insights for educators and curriculum developers who seek to improve teaching methodologies in the digital age.